2014
DOI: 10.1128/cvi.00680-13
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Interferon Immunospot Assay of Pleural Effusion Mononuclear Cells for Diagnosis of Tuberculous Pleurisy

Abstract: e Diagnosis of tuberculous pleurisy remains a challenge in the clinic. In this study, we evaluated the usefulness of a previously developed Mycobacterium tuberculosis antigen-specific gamma interferon enzyme-linked immunospot (ELISPOT) assay in the diagnosis of tuberculous pleurisy by testing a cohort of 352 patients with pleural effusion. We found that M. tuberculosis antigen-specific gamma interferon-producing cells were enriched four to five times in pleural fluid compared with their levels in peripheral bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 27 publications
2
41
1
Order By: Relevance
“…The full text of the remaining 10 articles was examined, and one study (Losi et al, 2010) was excluded because it did not use the t-spot assay format. The final meta-analysis therefore included nine publications (Losi et al, 2007;Lee et al, 2009;Dheda et al, 2009;Kang et al, 2012;Keng et al, 2013;Liao et al, 2014;Zhang et al, 2014;Liu et al, 2013Liu et al, , 2014 TN = truly negative result; TP = truly positive result; FN = false-negative result; FP = false-positive result. a Enzymelinked immunospot assay (T-SPOT-TB; Oxford Immunotec Ltd., Oxford, UK) measuring the immune response to an ESAT-6 or CFP-10 peptide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full text of the remaining 10 articles was examined, and one study (Losi et al, 2010) was excluded because it did not use the t-spot assay format. The final meta-analysis therefore included nine publications (Losi et al, 2007;Lee et al, 2009;Dheda et al, 2009;Kang et al, 2012;Keng et al, 2013;Liao et al, 2014;Zhang et al, 2014;Liu et al, 2013Liu et al, , 2014 TN = truly negative result; TP = truly positive result; FN = false-negative result; FP = false-positive result. a Enzymelinked immunospot assay (T-SPOT-TB; Oxford Immunotec Ltd., Oxford, UK) measuring the immune response to an ESAT-6 or CFP-10 peptide.…”
Section: Resultsmentioning
confidence: 99%
“…Despite extensive research on this assay, its diagnostic accuracy remains controversial. For example, one study reported a sensitivity of 95.7% and a specificity of 100% (Liao et al, 2014), while another study reported corresponding values of only 86 and 60% (Dheda et al, 2009). Since these accuracy studies were carried out with diverse sample sizes, patients of different ethnicities, and differing technical parameters (such as detection cut-offs), we wanted to assess the available evidence as rigorously and comprehensively as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the shortage of available methods for diagnosis of TB, IGRAs have increasingly been used as an auxiliary diagnostic tool for active TB in clinical practice in China (18,(31)(32)(33). Indeed, it has been reported that detection of IFN-␥ in pleural fluid mononuclear cells is useful for diagnosis of tuberculous pleurisy (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that detection of IFN-␥ in pleural fluid mononuclear cells is useful for diagnosis of tuberculous pleurisy (31,32). Additionally, IGRAs have improved the sensitivity for diagnosis of pulmonary TB (18), pediatric TB (34), and osteoarticular TB (33).…”
Section: Discussionmentioning
confidence: 99%
“…In this discussion, we would like to emphasize two additional items. We point the authors to another important study regarding this topic, which, as far as we know, was not included in their review (4). In addition, Aggarwal et al (1) appropriately describe that false positives may have compromised the specificity due to latent TB in non-TPE patients.…”
mentioning
confidence: 99%